CORPORATE SOCIAL RESPONSIBILITY IN INCOME TAX - Suparna Wijaya; Felicia Devi Anna Santi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Corporate Sosial Responsibility is the company's participation in sustainable economic development and the company's reciprocity to society and the environment. This research aims to understand the application of the taxable-deductible principle in CSR programs, find out the alternatives that companies can take in burden CSR costs, and find out what alternatives the government can do to harmonize CSR policies with tax regulations related to CSR costs. The method used is a qualitative research method. From the research results, it is known that the application of the taxable-deductible principle to CSR costs is not absolute, CSR costs can be taxable-deductible, nontaxable-nondeductible, taxable-nondeductible, or nontaxable-nondeductible. An alternative for taxpayers to be able to burden CSR cost is to choosing CSR programs that is allowed as deductible expense as stipulated in Article 6 paragraph (1) of the Income Tax Law. From the government's perspective, the main alternative that can be done to harmonize CSR policies with tax regulations is to make tax regulations that clearly regulate CSR, form a CSR Commission and/or require the preparation of a Sustainability Report for companies that want to charge CSR costs fiscally.